2024
DOI: 10.7554/elife.92063
|View full text |Cite
|
Sign up to set email alerts
|

Some mechanistic underpinnings of molecular adaptations of SARS-COV-2 spike protein by integrating candidate adaptive polymorphisms with protein dynamics

Nicholas James Ose,
Paul Campitelli,
Tushar Modi
et al.

Abstract: We integrate evolutionary predictions based on the neutral theory of molecular evolution with protein dynamics to generate mechanistic insight into the molecular adaptations of the SARS-COV-2 Spike (S) protein. With this approach, we first identified Candidate Adaptive Polymorphisms (CAPs) of the SARS-CoV-2 Spike protein and assessed the impact of these CAPs through dynamics analysis. Not only have we found that CAPs frequently overlap with well-known functional sites, but also, using several different dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 166 publications
0
1
0
Order By: Relevance
“…The results of this study provided molecular rationale and support to the experimental evidence that functionally balanced substitutions that optimize tradeoffs between immune evasion, high ACE2 affinity and sufficient conformational adaptability might be a common strategy of the virus evolution and serve as a primary driving force behind the emergence of new Omicron subvariants, including but not limited to BA. showing that Omicron variants can induce distinct dynamics and exploit epistatic interactions between sites R346, F486P, Q498, Q493 to modulate the RBD-ACE2 interface with increasing flexibility in antibody binding residues [118]. The results also demonstrated that L455, F456 and 58 Q493 are pronounced escape hotspots of resistance to class I antibodies.…”
Section: Discussionmentioning
confidence: 82%
“…The results of this study provided molecular rationale and support to the experimental evidence that functionally balanced substitutions that optimize tradeoffs between immune evasion, high ACE2 affinity and sufficient conformational adaptability might be a common strategy of the virus evolution and serve as a primary driving force behind the emergence of new Omicron subvariants, including but not limited to BA. showing that Omicron variants can induce distinct dynamics and exploit epistatic interactions between sites R346, F486P, Q498, Q493 to modulate the RBD-ACE2 interface with increasing flexibility in antibody binding residues [118]. The results also demonstrated that L455, F456 and 58 Q493 are pronounced escape hotspots of resistance to class I antibodies.…”
Section: Discussionmentioning
confidence: 82%